2014
DOI: 10.1152/jn.00549.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and cortical distribution of neural responses to 2D and 3D motion in human

Abstract: The perception of motion-in-depth is important for avoiding collisions and for the control of vergence eye-movements and other motor actions. Previous psychophysical studies have suggested that sensitivity to motion-in-depth has a lower temporal processing limit than the perception of lateral motion. The present study used functional MRI-informed EEG source-imaging to study the spatiotemporal properties of the responses to lateral motion and motion-in-depth in human visual cortex. Lateral motion and motion-in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…Given that these same cortical regions process not only visual motion signals but also the disparity and motion-in-depth signals that guide vergence tracking (e.g. Likova and Tyler, 2007; Rokers et al, 2009; Cottereau et al, 2011, 2014), our finding that the gain in vergence tracking is reduced in patients with schizophrenia is consistent with these previous findings. Further studies are therefore clearly needed that use psychophysics and fMRI to investigate the processing of both cyclopean and non-cyclopean disparity and motion-in-depth signals in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…Given that these same cortical regions process not only visual motion signals but also the disparity and motion-in-depth signals that guide vergence tracking (e.g. Likova and Tyler, 2007; Rokers et al, 2009; Cottereau et al, 2011, 2014), our finding that the gain in vergence tracking is reduced in patients with schizophrenia is consistent with these previous findings. Further studies are therefore clearly needed that use psychophysics and fMRI to investigate the processing of both cyclopean and non-cyclopean disparity and motion-in-depth signals in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the strongest activations measured for successful FfM perception and not observed for absent/failed FfM perception, were located in the parieto-occipital regions, part of the dorsal pathway, possibly corresponding to areas V3A and/or IPS. While parieto-occipital activity in response to FfM processing has not been reported in brain imaging studies (Schoenfeld et al 2003;Wang et al 1999;Gulyas et al 1994), these supplementary visual motion areas were found to be fundamental for 3D motion and more specifically for SfM processing (Vanduffel et al 2002;Orban et al 1999;Paradis et al 2000;Peuskens et al 2004;Gulyas et al 1994;Andersen 1989;Zhuang et al 2008;Brouwer and van Ee 2007;Cottereau et al 2014). Interestingly, overlapping activations for SfM and line drawings have been reported in an area located in the vicinity of the IPS region (Murray et al 2003), which suggests its potential role in processing related to form perception.…”
Section: Anatomical Perspectivementioning
confidence: 84%
“…Over the last years, the ROI-based approach described in this review has been used to characterize the dynamics and more recently the functional connectivity (Cottereau et al, 2014a) of the responses within the different visual areas. As an example, figure 4 shows the results obtained in one of our previous EEG studies where we were interested in the cortical mechanisms implied in decision-making (Cottereau et al, 2014b).…”
Section: Methodsmentioning
confidence: 99%
“…Functional ROI-based comparisons both simplify and increase the accuracy of the pooling of the results between subjects, because a co-registration of the individual anatomies, with its inevitable distortion is not necessary. Over the last several years, this approach has been used to study different properties of the visual system: motion processing (Cottereau et al, 2014a; Ales and Norcia, 2009), chromatic processing (Wang and Wade, 2011; Xiao and Wade, 2010), binocular disparity processing (Cottereau et al, 2011; 2012bc), attention (Kim and Verghese, 2012; Verghese et al, 2012; Palomares et al, 2012; Lauritzen et al, 2010), figure-ground segmentation (Appelbaum et al, 2006; 2008; 2010), perceptual decision-making (Cottereau et al, 2014b; Ales et al, 2013) and contrast normalization (Busse et al, 2009; Tsai et al, 2012). Beyond the scope of the visual system, this approach can easily be applied to other sensory systems where fMRI can be used to reliably map functional areas (see e.g.…”
Section: Introductionmentioning
confidence: 99%